Circulation of loyalty: Relationships between mobile messenger service and offline flagship store - Junghwan Kim; Mideum Choi; ShinYoung Hwang (International Telecommunications Society (ITS), 2018)
LINE, the global mobile messenger service provider, has been extending its online business to the offline platform. Among many services, LINE FRIENDS, which manages the character business of LINE, launched an offline flagship store in Korea, Japan, and Southeast Asia (LINE FRIENDS, 2018.01.25). Among the 45 stores around the world, LINE FRIENDS opened a large scale flagship store in New York in August 2017. Characters which were originally created for online stickers soon became the key business component of the flagship store. LINE FRIENDS has collaborated with renowned global brands such as LAMY, MR MARIA, THERMOS, SWAROVSKI, BROMPTON, and L'OCCITANE. People who visit offline flagship stores can not only buy collaboration products but also enjoy time at the character themed cafe. KAKAO which operates a major mobile messenger service in Korea has also launched its first flagship store in April 2014. Around 10 thousands visitors are reported to visit KAKAO's flagship store (KAKAO FRIENDS) every day...
Keywords: 330